THE IMPLEMENTATION OF THE MERDEKA CURRICULUM IN ENGLISH TEACHING AT SMAN 3 PANGKEP - Nurul Annisa Mahmud; Baso Jabu; Chairil Anwar Korompot (International Journal of Business English and Communication, 2025)
This study investigates the implementation of the Merdeka Curriculum in English language teaching at SMAN 3 Pangkep, focusing on teacher perceptions and challenges. Employing a descriptive qualitative approach, data were gathered through classroom observations and semi-structured interviews with three English teachers teaching grades X and XI under the Merdeka Curriculum framework. Findings reveal a partial success in adopting the curriculum's core principles, such as student-centered learning, integration of local cultural elements, and the use of diverse assessment methods. While teachers demonstrated efforts to engage students actively, disparities in curriculum implementation were observed. Challenges such as limited digital resources, lack of training, and infrastructure constraints affected teachers’ ability to fully integrate the curriculum's goals. This study concludes that while teachers at SMAN 3 Pangkep show openness to the curriculum’s objectives, enhanced support in terms of professional development and resources is essential for a consistent and effective application. These findings contribute valuable insights for improving curriculum implementation, supporting a more inclusive, engaging, and adaptive educational environment.